Social Workers' Stigmatic Perceptions of Individuals With Disabilities: A Focus on Three Disabilities. Issue 2 (3rd April 2017) - Werner, Shirli; Araten-Bergman, Tal
ABSTRACT: Introduction : People with disabilities often identify professionals' stigmatic views as significant barriers to accessing mainstream services. This study aimed to examine differences in stigmatic attitudes held by social workers toward individuals with intellectual disabilities (ID), mental illness (MI), or dual diagnosis (DD) of ID and MI. Methods : One hundred and fifty-eight social workers responded to three versions of a structured questionnaire. Participants were provided, in random order, with vignettes describing an individual with ID, MI, and DD, after which they completed the Attribution Questionnaire. Results : Results revealed a significant effect of disability type, so that individuals with MI were perceived to be more responsible for their condition than were individuals with ID or DD. Individuals with MI and DD were perceived as more dangerous than those with ID, and social workers endorsed more coercive and segregating behaviors toward individuals with MI and DD than toward those with ID. No differences were found in helping and avoidant behaviors in relation to disability type, and correlations between stigma constructs were found across all three disabilities. Conclusions : Findings are discussed in light of social workers' obligation to assist individuals to realize their rights to full social and civil inclusion. Given these obligations, they are expected to set aside their personal views and provide help to all their clients regardless of their diagnosis.